THE EVALUATION OF FUEL OR ELECTRICITY THROUGH THE MECHANICAL LOCOMOTIVE OPERATION - Korzhenevych, I. P. (Science and Transport Progress, 2009)
The relation of locomotive mechanical work with the consumption of fuel or electric power is considered.